Contagion at the interbank market with stochastic LGD - Christoph Memmel; Angelika Sachs; Ingrid Stein (Deutsche Bundesbank, 2011)
This paper investigates contagion at the German interbank market under the assumption of a stochastic loss given default (LGD). We combine a unique data set about the LGD of interbank loans with data about interbank exposures. We find that the frequency distribution of the LGD is u-shaped. Under the assumption of a stochastic LGD, simulation results show a more fragile banking system than under the assumption of a constant LGD. There are three types of banks concerning their tendency to trigger contagion: banks with strongly varying impact, banks whose impact is relatively constant, and banks with no direct impact.
Keywords: D53; E47; G21; 330; interbank market; contagion; stochastic LGD